A stringent test of the thermal coadaptation hypothesis in flour beetles. (August 2015) - Halliday, William D.; Blouin-Demers, Gabriel
Abstract: Whole-organism performance depends on body temperature and ectotherms have variable body temperatures. The thermal coadaptation hypothesis posits that thermal reaction norms have coevolved with thermal preference such that organisms attain optimal performance under a narrow range of body temperatures commonly experienced in the wild. Since thermal reaction norms are often similar, researchers interested in the effects of temperature on fitness often use one easily measured thermal reaction norm, such as locomotor performance, and assume it is a good proxy for fitness when testing the thermal coadaptation hypothesis. The extent to which this assumption holds, however, is often untested. In this study, we provide a stringent test of the thermal coadaptation hypothesis in red and in confused flour beetles by comparing the thermal reaction norm for reproductive output to the preferred body temperature range. We also test the assumption that locomotor performance can serve as a proxy for the thermal reaction norm for reproductive output, a more ultimate index of fitness. In both species, we measured the number of eggs laid, righting time, and sprint speed at eight temperatures, as well as the thermal preference in a thermal gradient. The number of eggs laid increased with female sprint speed and with male righting time, and all three performances had similar thermal reaction norms, with 80% of the maximum achieved between 23 and 37 °C. Red flour beetles had preferred body temperatures that matched the optimal temperature for performance; confused flour beetles had lower preferred body temperature than the optimal temperature for performance. We found support for the assumption that locomotor performance can serve as a proxy for reproductive output in flour beetles, but we only found evidence for thermal coadaptation in one of the two species. Highlights: One of the most stringent tests of the thermal coadaptation hypothesis to date. Test the assumption that locomotion is a good proxy for reproductive output. Red flour beetle thermal reaction norms matched their thermal preference. Confused flour beetle thermal reaction norms did not match their thermal preference. Righting time and sprint speed weakly predicted reproductive output.